Exploring the Impact of Intellectual Capital on University Students’ Digital Innovation Intentions: The Mediating Role of Digital Literacy in Indonesia - Irfan Wahzudi; Kurjono Kurjono (Universitas Negeri Padang, 2026)
The rapid expansion of the digital economy has increased the need for graduates who are capable of initiating digital innovation. However, educated unemployment remains a persistent challenge in Indonesia, suggesting that intellectual resources alone may not be sufficient to foster innovation-oriented intentions. This study examines the effects of knowledge and skills, networking, and opportunity recognition on the intention to start digital innovation, with digital literacy as a mediating variable. A quantitative survey was conducted among 334 university students from various higher education institutions in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that opportunity recognition significantly influences both digital literacy and intention to start digital innovation, while knowledge and skills significantly enhance digital literacy but do not directly affect innovation intention. Networking was found to have no significant effect on either digital literacy or innovation intention. Digital literacy significantly influences intention to start digital innovation and fully mediates the relationship between knowledge and skills and innovation intention, while partially mediating the effect of opportunity recognition. These findings highlight digital literacy as a critical capability-conversion mechanism through which intellectual capital is transformed into innovation-oriented intentions. The study extends Intellectual Capital Theory by emphasizing the role of digital literacy in converting intellectual resources into digital innovation intentions among university students.